Evaluation of the methacrylamide/ N’N,-methylenebisacrylamide binder system for gel-casting of titanium powder - Erasmus, W. (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.